Efficacy of Nifekalant in Patients With Wolff‐Parkinson‐White Syndrome and Atrial Fibrillation: Electrophysiological and Clinical Findings. Issue 13 (2nd July 2019) - Hu, Jinzhu; Yu, Jianhua; Chen, Qi; Hu, Jianxin; Huang, Qianghui; Xia, Zhen; Xia, Zirong; Ju, Zhenzhen; Yuan, Ping; Fan, Siyang; Xiong, Qinmei; Zhu, Bo; et al.
Abstract : Background: The efficacy of nifekalant in preexcited atrial fibrillation (AF) has not been assessed. Methods and Results: The study populations consisted of patients with sustained preexcited AF (n=51), paroxysmal supraventricular tachycardia (n=201), and persistent AF (n=87). Effects of intravenous infusion of nifekalant were assessed on electrophysiological and clinical parameters. Nifekalant prolonged the shortest preexcited R‐R, the average preexcited R‐R, and the average R‐R intervals from 290±35 to 333±44 ms, 353±49 to 443±64 ms, and 356±53 to 467±75 ms, respectively, in patients with preexcited AF (all P <0.001). Nifekalant also decreased the percentage of preexcited QRS complexes, heart rate, and increased systolic pressure (all P <0.001). Nifekalant terminated AF in 33 of 51 patients (65%). Similar effects were also observed in a subgroup of 12 patients with preexcited AF and impaired left ventricular function. In patients with paroxysmal supraventricular tachycardia, nifekalant significantly prolonged the effective refractory period, the block cycle length of the antegrade accessory pathway, and the atrial effective refractory period (all P <0.001). Nifekalant had no effect on the effective refractory period of the antegrade atrioventricular node. Finally, in patients with persistent AF without an accessory pathway, nifekalant did not significantly decrease the ventricular rate of AF. One patient developed Torsades de Pointes. No other adverse effects were observed. Conclusions: Nifekalant prolongs the effective refractory period of the antegrade accessory pathway and atrium without blocking antegrade conduction through the atrioventricular node, leading to slowing and/or to termination of preexcited AF. Thus, nifekalant might be an effective and a relatively safe drug in patients with preexcited AF.